Remarks on the Proportions and Dimensions Used in the Design of the Medieval Church of Zsámbék - Fehér, Krisztina; Halmos, Balázs (Periodica Polytechnica Architecture, 2019)
Since the 19th century, the church of Zsámbék was continuously a focus of scholars' interest. The present paper intends to research the church ruins with a new aspect. Using an accurate terrestrial laser scan survey, the geometry of the plan is analysed in order to find proportions among the dimensions. The main goal of the study is to gather information about the design logic of the first masters of the 13th-century Premonstratensian abbey. In addition, our goal was to detect contributions to the 13th-century construction history of the church, that cannot be found in archives of graphic sources. The latest archaeological excavation achieved excellent results concerning several crucial historical points; however, the periodization of the church is still not entirely clarified. From the 19th century, different scholars have proposed various hypotheses about this topic, without consensus.
Number: 2
Keywords: zsámbék

Zsámbéki premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2012)
Keywords: zsámbék